Wrecked destroyers, Point Honda (1923)
On September 8, 1923 US Navy ships ran aground at Point Honda near Lompoc, CA, resulting in 7 ships being destroyed and 23 deaths. It was the largest peacetime loss of Navy ships. Seen here is USS Chauncey